A.S.P.E.N. Clinical Guidelines: Nutrition Support of Hospitalized Adult Patients With Obesity. Issue 6 (23rd August 2013) - Choban, Patricia; Dickerson, Roland; Malone, Ainsley; Worthington, Patricia; Compher, Charlene; ,
Abstract : Background: Due to the high prevalence of obesity in adults, nutrition support clinicians are encountering greater numbers of obese patients who require nutrition support during hospitalization. The purpose of this clinical guideline is to serve as a framework for the nutrition support care of adult patients with obesity. Method: A systematic review of the best available evidence to answer a series of questions regarding management of nutrition support in patients with obesity was undertaken and evaluated using concepts adopted from the Grading of Recommendations, Assessment, Development and Evaluation working group. A consensus process, that includes consideration of the strength of the evidence together with the risks and benefits to the patient, was used to develop the clinical guideline recommendations prior to multiple levels of external and internal review and approval by the A.S.P.E.N. Board of Directors. Questions: (1) Do clinical outcomes vary across levels of obesity in critically ill or hospitalized non−intensive care unit (ICU) patients? (2) How should energy requirements be determined in obese critically ill or hospitalized non‐ICU patients? (3) Are clinical outcomes improved with hypocaloric, high protein diets in hospitalized patients? (4) In obese patients who have had a malabsorptive or restrictive surgical procedure, what micronutrients should be evaluated?